The Effect of Infaq Habits on Spiritual Intelligence In Early Childhood at PAUD IT Aladuna 2 Bengkulu City - Syahfira Nur Insani; Evi Selva Nirwana (Peneliti.net, 2023)
The purpose of this study was to determine the effect of giving infaq habituation on Spiritual Intelligence (SQ). This study used an experimental method with a 2x2 factorial design, the large sample used in the study was 13 children in class B1 and 13 children in class B3 PAUD IT Auladuna 2 Bengkulu City, so the total sample was 26 children in the 2022/2023 school year. The habit of giving infaq can affect the ability of spiritual intelligence (SQ) in early childhood at PAUD IT Auladuna 2 Bengkulu City, it can be seen from the SPSS 25 program that the mean price of children who have an awareness of giving infaq is 19.2500; The standard deviation is 1.33278, this price already shows that some of the children in PAUD IT Auladuna 2 have well-developed awareness of giving and can be seen from the experimental class and the control class group. So that the sample obtained is 13 people from the control class and 13 people from the experimental class. The results of the observations of researchers in the experimental group (posttest) experienced a higher increase compared to the control group (pretest). receiving the treatment of infaq activities decreased by 50%. This is evidenced by the difference in the increase in the average value of children and the proportion of each meeting has increased and also proven by the t test that there is a very significant difference in spiritual intelligence of α : 6.51 < 0.05 significant level. The results achieved in the habit of giving infaq greatly influence spiritual intelligence in early childhood at PAUD IT Auladuna Bengkulu City